Infodemic, the other pandemic during 2019 coronavirus disease - Arroyo-Sánchez, Abel Salvador (2020)
Infodemia is the information epidemy associated to fear, speculation and rumors, amplified and transmitted rapidly by modern information technologies and that negatively affects society. Its association with the 2019 Coronavirus Disease pandemic is not exclusive, as it had already been described with the Coronavirus-1 Severe Acute Respiratory Syndrome pandemic in 2003. This false or misleading information may cause public reluctance widespread adoption of infection control measures promoted by health authorities, and thus delaying essential recomendations. The World Health Organization (WHO), in its eagerness to counteract, has established the WHO Information Network to Epidemics.